O impacto das oficinas de estratégias de leitura na motivação para o empréstimo de obras da Biblioteca Regional da UFMT - Santana, Geisiane Dias de (2020)
The present research is linked to the line "Languages, culture and knowledge construction: historical and contemporary perspectives" and to the research group “Alfabetização e Letramento Escolar (ALFALE)” of the Graduate Program in Education of the University Campus of Rondonópolis, Federal University of Mato Grosso (PPGEdu/CUR/UFMT). The theme of this research is the reading acts of academics at the Federal University of Mato Grosso, with emphasis on the frequency of borrowed works at the Regional Library of the Campus. During the course chosen, the academic, through the resources offered by the institution, needs to look for alternatives that can help in the better understanding of the technical texts of the graduation, after all, they require a higher level of reading proficiency. In view of the above, the guiding question of this research was: What are the impacts of the Reading Strategies Workshops on the motivation to borrow works from the Regional Library of the University Campus of Rondonópolis? The study aims at understanding the impact of the Reading Strategies Workshops on the motivation for the borrowing of works of the Regional Library of the University Campus of Rondonópolis. Aiming at reaching the main objective, it was necessary: a) To identify the reading and writing profile of the Library users; b) To map the lending and file consulting habits of the research collaborators. Through the objectives, the nature of this research was defined as being explanatory, of experimental character, with survey design and the data treatment, through qualitative approach. For this purpose, organized study activities called "Reading Strategies Workshops for Higher Education Students" were carried out. The public consisted of 25 academics, 14 of whom were students of Pedagogy and 11 of Portuguese. Among them, eight participants were selected considering that they answered affirmatively to the two questions that turned to measuring the impact of the workshops in the motivation to borrow works of the Regional Library of UFMT. In general, the data indicated that actions that go beyond the scope of the Library itself are important to awaken the academic to the use of this reading space, but they are not enough, since joint actions should be proposed between the courses and the Library, in order to foster dialogue between them, enriching them mutually.